The Water Craze - Bernard Lown (South African Family Practice)
I was taken aback when an elderly patient confessed dejectedly that she didn’t drink the eight glasses of water her physician had prescribed. I was astounded to learn that water loading for all comers pervades medical practice. But how robust is the scientific evidence, and how did this come about? Innovations in clinical practice are usually based on accumulations of scientific breakthroughs. These are first published in medical journals and then trumpeted 24/7 in the media. Yet I could not recall a single scientific study on the benefits of increased water consumption.